An Evaluation of English for Medical Purposes Materials in Language Training Institutions: A Needs-Based Approach - Sukisno, Sukisno; Lustyantie, Ninuk; Murtadho, Fathiaty (LPPM Institut Pendidikan Nusantara Global, 2025)
This study evaluates English for Medical Purposes (EMP) materials used in language training institutions through a needs-based approach. Using a mixed-methods design, the research gathered data from medical students, instructors, and clinical supervisors to assess the relevance and effectiveness of EMP materials. Quantitative analysis revealed that while several units (e.g., “In and Around the Hospital,” “Admissions,” and “Monitoring the Patient”) effectively reflect authentic professional communication, others lacked contextual depth and interactive tasks. Qualitative insights highlighted strengths in authentic scenarios and practical dialogues, as well as gaps in empathetic and interprofessional communication training. The findings underscore the importance of aligning EMP materials with real-world clinical needs by integrating communicative competence, cultural appropriateness, and professional authenticity. This study provides recommendations for enhancing EMP curricula to support healthcare professionals in developing the language skills essential for patient-centered care and interdisciplinary collaboration.